Operational lessons learned in conducting a multi-country collaboration for vaccine safety signal verification and hypothesis testing: The global vaccine safety multi country collaboration initiative. Issue 3 (8th January 2018) - ,; Kuli-Lito, Georgina; Kostaqi, Entela; Petrela, Elizana; Castellano, Vanesa E.; Chiarvetti, Lucia; Falcó, Adriana; Gentile, Angela; Guirau, Karina; Carrega, Maria Eugenia Pérez; Rasjido, Susana; Testino, Sofía; et al.
Abstract: Timely and effective evaluation of vaccine safety signals for newly developed vaccines introduced in low and middle- income countries (LMICs) is essential. The study tested the development of a global network of hospital-based sentinel sites for vaccine safety signal verification and hypothesis testing. Twenty-six sentinel sites in sixteen countries across all WHO regions participated, and 65% of the sites were from LMIC. We describe the process for the establishment and operationalization of such a network and the lessons learned in conducting a multi-country collaborative initiative. 24 out of the 26 sites successfully contributed data for the global analysis using standardised tools and procedures. Our study successfully confirmed the well-known risk estimates for the outcomes of interest. The main challenges faced by investigators were lack of adequate information in the medical records for case ascertainment and classification, and access to immunization data. The results suggest that sentinel hospitals intending to participate in vaccine safety studies strengthen their systems for discharge diagnosis coding, medical records and linkage to vaccination data. Our study confirms that a multi-country hospital-based network initiative for vaccine safety monitoring is feasible and demonstrates the validity and utility of large collaborative international studies to monitor the safety of new vaccines introduced in LMICs.